Identifying 5 Common Psychiatric Disorders Associated Chemicals Through Integrative Analysis of Genome-Wide Association Study and Chemical-Gene Interaction Datasets. (15th April 2020) - Cheng, Shiqiang; Wen, Yan; Ma, Mei; Zhang, Lu; Liu, Li; Qi, Xin; Cheng, Bolun; Liang, Chujun; Li, Ping; Kafle, Om Prakash; Zhang, Feng
Abstract: Psychiatric disorders are a group of complex psychological syndromes whose etiology remains unknown. Previous study suggested that various chemicals contributed to the development of psychiatric diseases through affecting gene expression. This study aims to systematically explore the potential relationships between 5 major psychiatric disorders and more than 11 000 chemicals. The genome-wide association studies (GWAS) datasets of attention deficiency/hyperactive disorder (ADHD), autism spectrum disorder (ASD), bipolar disorder (BD), major depression disorder (MDD), and schizophrenia (SCZ) were driven from the Psychiatric GWAS Consortium and iPSYCH website. The chemicals related gene sets were obtained from the comparative toxicogenomics database (CTD). First, transcriptome-wide association studies (TWAS) were performed by FUSION to calculate the expression association testing statistics utilizing GWAS summary statistics of the 5 common psychiatric disorders. Chemical-related gene set enrichment analysis (GSEA) was then conducted to explore the relationships between chemicals and each of the psychiatric diseases. We observed several significant correlations between chemicals and each of the psychiatric disorders. We also detected common chemicals between every 4 of the 5 major psychiatric disorders, such as androgen antagonists for ADHD ( P value = .0098), ASD ( P value = .0330), BD ( P value = .0238), and SCZ ( P value = .0062), and imipramine for ADHD ( P value = .0054), ASD ( P value = .0386), MDD ( P value = .0438), and SCZ ( P value = .0008). Our study results provide new clues for revealing the roles of environmental chemicals in the development of psychiatric disorders.